Estudo epidemiológico da infecção pelo vírus da imunodeficiência felina em gatos domésticos da região sul do Rio Grande do Sul - Silva, Fábio da Silva e (2012)
The feline immunodeficiency virus belongs to the Retroviridae family, Lentivirus gennus and presents molecular structure and pathogenicity similar to the human immunodeficiency virus (HIV), therefore it is not transmissible to humans, being susceptible only the domestic and feral cats. FIV is classified in five phylogenetically different subtypes from A to E spread worldwide, apart from recombinant strains among the subtypes. Recently, two new subtypes were described, the subtype F identified in the United States and Portugal, and the subtype U-NZenv in New Zealand. Considering that the retroviruses have the ability to integrate the cell genome, under double stranded DNA form, it is possible to detect the provirus in infected leucocytes through the polymerase chain reaction (PCR) technique. The present report investigated the occurrence of the feline immunodeficiency virus infection between 2010 and 2011 in domestic cats submitted to medical treatment at the Hospital of Veterinary Clinics of the Federal University of Pelotas and private clinics from Pelotas, RS. Blood samples of seventy animals, healthy or sick, were collected and subjected to the nested-PCR technique. The tested cats were classified in two groups taking into account their clinical condition: the group 1 represented 28 FIV suspect cats with lymphadenomegaly, neurological disorders or chronic and recurring infections. The results pointed out a FIV infection frequency of 15,7% (11/70). Eight of the positive samples were subjected to molecular characterization, being all of them into the subtype B. The most diagnosed clinical manifestations in the cats that developed disease related to FIV were bronchopulmonar (4/10) and cutaneous (3/10) secondary infections. Another clinical disorders observed in the positive animals were gingivitis, uveitis, anemia and icterus. The FIV infected cats presented 30% of lethality during the period of study. Most of the infected cats were up to 10 years of age. Faced with the data shown in this report we could conclude that the subtype B of the feline immunodeficiency virus presents circulation in the domestic cat population of the south region of Rio Grande do Sul and elderly animals affected by chronic or recurring infections must be FIV tested.